1986
DOI: 10.1093/jn/116.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Dietary Manganese and Copper Deficiency on Rat Skeleton

Abstract: Experiments were designed to produce biochemical changes in both serum and bone in rats by long-term dietary deficiencies of manganese (Mn) and copper (Cu). Weanling rats were fed one of three diets: 1) normal Mn and Cu (N), 2) low Mn and Cu (L) and 3) depleted Mn and normal Cu (D). After 12 mo, serum Ca and P were significantly greater in the D rats than the N rats (134, 50 mg/L and 103, 39 mg/L, respectively). Serum and femur Mn levels were lower in D rats than in normal rats. Serum and femur Cu levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 24 publications
1
43
1
3
Order By: Relevance
“…However, there is some evidence that Cu de®ciency in¯uences bone resorption. An increased rate of bone resorption has been suggested as one explanation for the reduced bone mass observed in Cu-de®cient rats (Strause et al, 1986). Furthermore, studies carried out in vitro have shown that Cu reduces active bone resorption, as measured by release of 45 Ca or hydroxyproline into the bathing medium from cultured explanted 45 Ca-labelled mouse calvaria bone grown in medium with or without the addition of Cu (Wilson et al, 1981;Katz et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some evidence that Cu de®ciency in¯uences bone resorption. An increased rate of bone resorption has been suggested as one explanation for the reduced bone mass observed in Cu-de®cient rats (Strause et al, 1986). Furthermore, studies carried out in vitro have shown that Cu reduces active bone resorption, as measured by release of 45 Ca or hydroxyproline into the bathing medium from cultured explanted 45 Ca-labelled mouse calvaria bone grown in medium with or without the addition of Cu (Wilson et al, 1981;Katz et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts are known to produce superoxide and decreased activities of this enzyme could conceivably lead to increased bone resorption (Rico, 1991). An increased rate of bone resorption has been suggested as one explanation for the reduced bone mass observed in Cu-de®cient rats (Strause et al, 1986). Furthermore, studies carried out in vitro have shown that Cu reduces active bone resorption, as measured by release of 45 Ca or hydroxyproline into the bathing medium from cultured explanted 45 Ca-labelled mouse calvaria bone grown in medium with or without the addition of Cu over a 48 h period (Wilson et al, 1981;Katz et al, 1984).…”
Section: Dietary Cu Supplementation and Bone Biomarkersmentioning
confidence: 99%
“…[42]. В эксперименте эффекты долгосрочно-го дефицита марганца и меди в диете включают снижение минерализации в сочетании с увеличе-нием резорбции кости [43]. Хронический дефицит марганца и меди приводит к снижению активно-сти строящих кость остеобластов, увеличению резорбции костного матрикса и, следовательно, снижению плотности и массы костей.…”
Section: марганец и структура стunclassified
“…Рентгенограммы плечевых костей указали на присутствие многочисленных очагов повреж-дения кости как при сочетанном дефиците Mn/Cu, так и при глубоком дефиците марганца (рис. 4) [43].…”
Section: марганец и структура стunclassified
See 1 more Smart Citation